Gestión de desarrollo familiar en función a la producción de pitahaya (Hylocereus undatus) en el Ecuador - Mora Andrade, Ariel Stalin (2023)
Dragon fruit production in Ecuador presents significant potential but faces challenges that particularly affect low-income families. For this reason, the study focused on the topic of “Family development management based on the production of pitahaya (Hylocereus undatus) in Ecuador”, where important material on pitahaya was analyzed and investigated from its generalities, its derivatives and the forms. how families in Ecuador develop it. For this purpose, specific objectives were followed and based on the descriptive and documentary methodology, the conclusion was obtained that pitahaya is a growing business in Ecuadorian families and that it is extremely important to continue exploiting this fruit that has many openings in different international markets. , the only obstacle being financing, which with adequate technical help is resolved by being a source of solid income for Ecuadorian families that will allow them for better sustainable and social development, which is why pitahaya production in Ecuador is not only a source valuable income source, but also has the potential to diversify the country's agricultural economy and strengthen food security and rural development. However, to make the most of these opportunities, it is crucial to provide adequate support to the families involved.